Does transparency about banks’ lending costs lower firms’ borrowing costs? Evidence from India - Tantri, Prasanna; Vishen, Nitin (Journal of Accounting and Economics, 2025)
We study the impact of transparency about banks’ costs on loan interest rates. The Indian Central Bank required banks to disclose a cost-based benchmark interest rate instead of the prime rate. The banks could price loans using any spread to the cost-based benchmark. We find that this change, which made banks’ cost structures more transparent, lowers the interest rates charged and leads to increases in debtor firms’ total borrowings and investments. We hypothesize that increased cost transparency reveals relationship rents to competitor banks and makes it difficult for incumbent banks to maintain high relationship rents because of increased threat of entry.